2008
DOI: 10.1021/es800091f
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Oxide Nanoparticles in a Model Wastewater Treatment Plant: Influence of Agglomeration and Surfactants on Clearing Efficiency

Abstract: The rapidly increasing production of engineered nanoparticles has created a demand for particle removal from industrial and communal wastewater streams. Efficient removal is particularly important in view of increasing long-term persistence and evidence for considerable ecotoxicity of specific nanoparticles. The present work investigates the use of a model wastewater treatment plant for removal of oxide nanoparticles. While a majority of the nanoparticles could be captured through adhesion to clearing sludge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
215
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 440 publications
(226 citation statements)
references
References 53 publications
7
215
0
4
Order By: Relevance
“…Heteroaggregation could occur between a single particle and a cell, or via particle aggregate-cell interactions [114] -with important implications in the natural environment. For instance, NPs-microorganism heteroaggregation can lead to increased removal of NPs from wastewater during secondary treatment [106,[115][116][117][118]. Interactions between cell walls of microorganisms and NPs are also thought to precede uptake and toxicity [107,108,[110][111][112]116,119], and may be important for trophic transfer of NPs in both aquatic and terrestrial environments [108,[119][120][121].…”
Section: Heteroaggregation Between Nanoparticles and Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heteroaggregation could occur between a single particle and a cell, or via particle aggregate-cell interactions [114] -with important implications in the natural environment. For instance, NPs-microorganism heteroaggregation can lead to increased removal of NPs from wastewater during secondary treatment [106,[115][116][117][118]. Interactions between cell walls of microorganisms and NPs are also thought to precede uptake and toxicity [107,108,[110][111][112]116,119], and may be important for trophic transfer of NPs in both aquatic and terrestrial environments [108,[119][120][121].…”
Section: Heteroaggregation Between Nanoparticles and Microorganismsmentioning
confidence: 99%
“…EPS, dissolved or bound to cell wall [124] have been shown to affect the physicochemical properties and stability of ENMs [15,22,58,125], and can also mediate heteroaggregation between NPs (and other nanomaterials) and cells [114,116,119]. Environmental factors such as media ionic strength, pH, and NOM or other dispersing agents can also influence heteroaggregation between NPs and microorganisms [107,[114][115][116]. For instance, Ma et al [114] showed that the anatase form of TiO 2 formed strong heteroaggregates with Chlorella pyrenoidosa at near neutral conditions (pH 6.8) but not at acidic or alkaline conditions.…”
Section: Heteroaggregation Between Nanoparticles and Microorganismsmentioning
confidence: 99%
“…Nanowaste is treated directly or indirectly. For instance, wastewater treatment plants efficiently transfer engineered nanoparticles from wastewater to sludge 10,11 , which is sometimes then incinerated. We do not yet know the fate and removal efficiency of nanoparticles in large-scale incinerators.…”
mentioning
confidence: 99%
“…Nanomaterials can enter the human body by various routes, such as breathing, eating, and touching the skin (Figure 2) [4][5][6][7][8]29,45]. Skin is the first defense barrier against the outside environment and is typically the first place on the body that is exposed to nanomaterial toxicity.…”
Section: Toxicity Of Nanomaterials and Lung Diseasementioning
confidence: 99%